Left Ventricular Function Recovery After Transapical TAVR in Patients With Previous Coronary Artery Bypass Graft Surgery. Issue 5 (October 2019) - Okoh, Alexis K.; Sossou, Christoph; Kang, Nathan; Decker, Jonathan; Dave, Devangi; Haik, Bruce; Chen, Chunguang; Cohen, Marc; Russo, Mark
Objective: The transapical (TA) approach is an alternative access technique for transcatheter aortic valve replacement (TAVR) in patients with symptomatic aortic valve stenosis. The impact of prior coronary artery bypass graft (CABG) surgery and how it affects left ventricular function recovery is not well defined. Methods: Patients who had TAVR at a single center between June 2012 and December 2016 were reviewed. High-risk patients who underwent the procedure via a TA approach were divided into 2 groups based on their history of CABG surgery. Postoperative outcomes were compared between groups. CABG/TA-TAVR patients were subdivided into 2 per baseline left ventricular ejection fraction (LVEF) <50%. The changes in LVEF and valve function at follow-up (1 to 12 months) were analyzed using paired t -tests. Results: Of 923 cases in total, 183 (19.8%) were performed via a TA approach. The mean ± SD Society of Thoracic Surgeons risk score of TA patients was 10.2 ± 4.6. Forty-nine (27%) had a surgical history of CABG. Overall all-cause mortality rates at 30 days, 1 year, and 2 years were similar for both groups ( P = 0.59, P = 0.64, P = 0.78). Subgrouping of CABG-TAVR patients ( n = 49) identified 24 patients (49%) with LVEF ≥50% vs. 25 (51%) with LVEF <50%. At 1-year follow-up, significant improvements in LVEF (low LVEF group) and valve function for both groups were observed. LVEF ≥50% group (LVEF: ∆ : −3%, P = 0.878; aortic valve area [AVA]: ∆ : 1.3 cm 2, P < 0.001; mean gradient: ∆ : −38 mmHg, P < 0.001); LVEF <50% group (LVEF: ∆ : 10%, P = 0.01; AVA: ∆ : 1.3 cm 2, P < 0.001; MG: ∆ : −31 mmHg, P < 0.001). Conclusions: TA-TAVR can be safely performed with acceptable postoperative outcomes in patients with a history of CABG surgery. In those with reduced EF, significant improvements in LV and valve functions are seen at 1-year follow-up.